Tamoxifen antagonizes proliferation and invasion of estrogen receptor-negative metastatic follicular thyroid cancer cells via protein kinase C - Hölting, Thomas; Duh, Quan-Yang; Clark, Orlo H.; Herfarth, Christian (Cancer letters, 1996)
Tamoxifen inhibits invasion and growth of estrogen-receptor negative follicular thyroid cancer (FTC) cells in vitro and in vivo. To study the mechanisms involved, we documented the effects of tamoxifen and staurosporine on three metastatic FTC-cell lines. TPA(10 ng/ml) enhanced invasion and growth of FTC by 15% (Pb < 0.02). Tamoxifen (1.5 μmol/l) inhibited invasion of FTC133 by 36% (FTC236 30%; FTC238 32%; P < 0.01). TPA reversed the tamoxifen-mediated inhibition of invasion by 35% in FTC133 and 30% in FTC238 (P < 0.02). Staurosporine (10 ng/ml) inhibited invasion and growth of all FTC. At 0.1-1 ng/ml it enhanced the inhibitory effects of tamoxifen, but did not further inhibit invasion or growth at higher concentrations. We conclude that the antiproliferative and antiinvasive effects of tamoxifen on follicular thyroid cancer cells are at least partly mediated by an inhibition of protein kinase C.